Effects of historically familiar and novel predator odors on the physiology of an introduced prey - Mella, V.; Cooper, C.; Davies, Stephen (Current Zoology Editorial Office, 2016)
© The Author (2016). Published by Oxford University Press. Predator odors can elicit fear responses in prey and predator odor recognition is generally associated with physiological responses. Prey species are often more likely to respond to the odor of familiar rather than alien predators. However, predator naïvety in an introduced prey species has rarely been investigated. We examined the physiological response, as shown by changes in ventilatory variables, of an introduced terrestrial herbivore, the European rabbit Oryctolagus cuniculus, in Australia, to the odor of potential predators and to control odors (distilled water and horse), to explore if responses were limited to historical (cat and fox) predators, or extended to historically novel predators (snake and quoll). All odors except distilled water elicited a response, with rabbits showing long-term higher respiratory frequencies and lower tidal volumes after introduction of the odors, indicating an increase in alertness. However, the intensity of the rabbits' reaction could not be directly linked to any pattern of response with respect to the history of predator-prey relationships. Rabbits exhibited significantly stronger reactions in response to both cat and quoll odors than they did to distilled water, but responses to horse, fox, and snake odor were similar to that of water. Our results show that the introduced rabbit can respond to both historical and novel predators in Australia,and suggest that shared evolutionary history is not necessarily a prerequisite to predator odor recognition.